Parametric Study of Turbulent Couette Flow over Wavy Surfaces Using RANS Simulation: Effects of Aspect-Ratio, Wave-Slope and Reynolds Number - Akshay Sherikar; Peter J. Disimile (Fluids, 2020)
A turbulent Couette flow over a wavy surface is subject to a detailed parametric study in which three parameters—Aspect Ratio, Wave Slope and Reynolds number—are independently varied over an order of magnitude to investigate their influence on the flow. Stdk−ε turbulence model with enhanced wall functions is used to simulate all cases in the study and the results are validated against experimental data as well as analytical theories pertaining to flow over wavy surfaces. Gross flow properties such as mean velocity profiles, mass flow rate, shear stress and pressure on the walls, as well as turbulent flow characteristics such as inner-wall coordinates, log-law fit, eddy viscosity profiles and turbulence kinetic energy across the domain, are presented and their corroboration with existing literature is discussed. The effect of the three parameters on the flow variables is investigated. It is observed that while all response flow variables scale monotonically with a progressive change in the parameters, there are certain flow characteristics that can be ascribed exclusively to one of the three parameters. The study also discusses the influence of the top plate, a much-needed discussion that seems to be absent in most literature pertaining to Couette flow in wavy channels.